Muslim Tatar minorities in the Baltic Sea Region - Svanberg, Ingvar, 1953-; Westerlund, David. (Muslim Minorities, 2015)
In Muslim Tatar Minorities in the Baltic Sea Region , edited by Ingvar Svanberg and David Westerlund, the contributors introduce the history and contemporary situation of these little known groups of people that for centuries have been part of the religious and ethnic mosaic of this region. The book has a broad and multi-disciplinary scope and covers the early settlements in Lithuania and Poland, the later immigrations to Saint Petersburg, Finland, Estonia and Latvia, as well as the most recent establishments in Sweden and Germany. The authors, who hail from and are specialists on these areas, demonstrate that in several respects the Tatar Muslims have become well-integrated here. Contributors are: Toomas Abiline, Tamara Bairasauskaite, Renat Bekkin, Sebastian Cwiklinski, Harry Halén, Tuomas Martikainen, Agata Nalborczyk, Egdunas Racius, Ringo Ringvee, Valters Scerbinskis, Sabira Ståhlberg, Ingvar Svanberg and David Westerlund.